Géographie du changement social en Égypte - Delphine Pagès-El Karoui (EchoGéo)
In Egypt, as in the Arab world, the strong dynamics of social change have remained invisible for many western observers, for whom the 2011 uprisings were impossible to understand, rather miraculous. This paper aims to explore the changes upstream of the revolution and its new landscapes. It focuses first on the structural changes, i.e. the individualization of the society –facilitated by a deep urbanization–, analyzed here at the family and religious levels. It deals also with the role of global economic transformations (liberalization, the rise of consumption and leisure society, new technologies). Then, it questions the role of one category of agents, the migrants, usually depicted in Egyptian media as scapegoats of social change.